Production and use of rapid responses during the COVID-19 pandemic in Quebec (Canada): perspectives from evidence synthesis producers and decision makers - Esther McSween-Cadieux; Julie Lane; Quan Nha Hong; Andrée-Anne Houle; François Lauzier-Jobin; Eliane Saint-Pierre Mousset; Ollivier Prigent; Saliha Ziam; Thomas Poder; Alain Lesage; Pierre Dagenais (BMC, 2024)
Abstract Background The COVID-19 pandemic has required evidence to be made available more rapidly than usual, in order to meet the needs of decision makers in a timely manner. These exceptional circumstances have caused significant challenges for organizations and teams responsible for evidence synthesis. They had to adapt to provide rapid responses to support decision-making. This study aimed to document (1) the challenges and adaptations made to produce rapid responses during the pandemic, (2) their perceived usefulness, reported use and factors influencing their use and (3) the methodological adaptations made to produce rapid responses. Methods A qualitative study was conducted in 2021 with eight organizations in the health and social services system in Quebec (Canada), including three institutes with a provincial mandate. Data collection included focus groups (n = 9 groups in 8 organizations with 64 participants), interviews with decision makers (n = 12), and a document analysis of COVID-19 rapid responses (n = 128). A thematic analysis of qualitative data (objectives 1 and 2) and a descriptive analysis of documents (objective 3) were conducted. Results The results highlight the teams and organizations' agility to deal with the many challenges encountered during the pandemic (e.g., increased their workloads, adoption of new technological tools or work processes, improved collaboration, development of scientific monitoring, adaptation of evidence synthesis methodologies and products). The challenge of balancing rigor and speed was reported by teams and organizations. When available at the right time, rapid responses have been reported as a useful tool for informing or justifying decisions in a context of uncertainty. Several factors that may influence their use were identified (e.g., clearly identify needs, interactions with producers, perceived rigor and credibility, precise and feasible recommendations). Certain trends in the methodological approaches used to speed up the evidence synthesis process were identified. Conclusions This study documented rapid responses producers' experiences during the COVID-19 pandemic in Quebec, and decision makers who requested, consulted, or used these products. Potential areas of improvements are identified such as reinforce coordination, improve communication loops, clarify guidelines or methodological benchmarks, and enhance utility of rapid response products for decision makers.